Variability of Crop Residues Determines Solubilization and Availability of Phosphorus Fractions during Composting of Rock Phosphate Enriched Compost Vis-à-vis Ordinary Compost. Issue 15 (21st August 2020) - Moharana, Pravash Chandra; Biswas, Dipak Ranjan; Ghosh, Avijit; Sarkar, Abhijit
ABSTRACT: The aims of this study were to see the effect of variability of crop residues viz ., rice straw, wheat straw, mustard stover, chickpea stover and tree leaves on solubilization and availability of phosphorus (P) fractions during composting of rock phosphate enriched composting (RPEC) vis-a-vis ordinary compost; to propose suitable bioavailable index for RPEC; and to recommend the maturity time of RPEC for its field application to maximize P availability. Results revealed that the rice straw-RPEC had higher total N and lower C/N ratio than composts prepared with other crop residues. Total and available P fractions were higher in RPEC than ordinary compost. The concentration of bioavailable P increased significantly in RP-enriched composts of rice straw, wheat straw, chickpea stover and mustard stover during composting. The distribution indicated that citrate-soluble P (CSP) was the major component of the bioavailable P during composting. The efficiency of crop residues in enhancing P solubilization from RP followed the order: rice straw > chickpea stover > wheat straw > mustard stover > tree leaves. Solubilization trend indicated that 90-days-old compost would maximize P availability in RPEC and could be applied in field to maximize P availability. The bioavailable indices as obtained from the ratios of total organic C (TOC) to total P (TOC/TP), water-soluble C (WSC) to total P (WSC/TP) and total organic C to citrate soluble P (TOC/CSP) correlated well with Olsen-P (NaHCO3 -P) and water-soluble P (WSP) of RPEC. Thus, we recommend these ratios as the bioavailable indices of P.